Perlindungan Hukum Pemilik Benda Gadai Yang Bendanya Dijadikan Objek Gadai Oleh Orang Lain Tanpa Persetujuannya (Jurnal Begawan Hukum (JBH), 2024)
Basically, the only person who can pawn an object is the owner of the object, but now incidents have become widespread where other people pawn objects that do not belong to them without the consent of the owner of the object. In this case, the owner of the object can file a lawsuit for revindication when the object is taken by someone else. However, Article 1977 paragraph (1) BW states that whoever controls a movable object is considered the owner. Given these legal problems, this research wants to examine the legal protection of owners of pawned objects whose objects are used as pawn objects by other people without their consent. This research aims to analyze the applicability of the Nemo Plus Juris Transferre Potest Quam Ipse Habet principle as a basis for encumbrances on pledged objects without the consent of the owner of the object as well as legal protection for the owner of the object and the recipient of the pledge when the object is used as an object of pawn by another person without the knowledge of the owner of the object. The research method used in this research is normative legal research using a statutory approach and a conceptual approach. This research uses primary and secondary legal sources by collecting through literature studies which are then analyzed using descriptive analytical methods. The results of the research are that the agreement made by the pawnbroker and the debtor who is not the owner of the object is valid because the validity of the pledge is determined by handing over the pawned object to the creditor and the creditor cannot be blamed if he receives an unregistered movable object in good faith.